2019
DOI: 10.31557/apjcp.2019.20.9.2775
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Hematological Relevance of JAK2V617F, CALR, and MPL Mutations in Vietnamese Patients with Essential Thrombocythemia

Abstract: Background: The picture of Vietnamese patients with essential thrombocythemia (ET) remains mostly undetermined. Our study intended to determine the frequency of JAK2V617F, CALR exon 9, and MPL exon 10 mutations as well as to analyze clinical characteristics associated with different mutational status in Vietnamese ET patients. Methods: We explored mutations of JAK2V617F, MPL, and CALR from 395 patients using allele specific oligonucleotide-polymerase chain reaction and Sanger sequencing techniques; then, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
5
8
0
Order By: Relevance
“…In the current study, no statistically significant difference in age and gender was observed among different genotypes. This finding is in agreement with earlier reports [4,5,7,8,10,16,20]. Similar to previous reports, patients with mutated JAK2 V617F showed significantly higher hemoglobin levels, white blood cell count, and platelet count compared to patients with other driver mutations and triple negative patients [6-8, 10, 16, 20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, no statistically significant difference in age and gender was observed among different genotypes. This finding is in agreement with earlier reports [4,5,7,8,10,16,20]. Similar to previous reports, patients with mutated JAK2 V617F showed significantly higher hemoglobin levels, white blood cell count, and platelet count compared to patients with other driver mutations and triple negative patients [6-8, 10, 16, 20].…”
Section: Discussionsupporting
confidence: 93%
“…Also, some researchers observed a lower frequency of JAK2 V617F mutation (31%) [18] and (35.7%) [19]. In the current series, the frequency of CALR (22%) is consistent with earlier reports [15,[20][21][22][23][24] but, higher than previous reports from Korea (17.7 %) [8], and Italy (14%) [25]. In concern to MPL W515L mutation, our observation (16.4%) is higher than earlier records that ranged from 1% to 14% [18,[25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…In a study including 102 ET patients, females were reported to more frequently harbor the JAK2V617F mutation and JAK2V617F-mutated patients were found to be older and had higher leucocyte counts [25].Another study including 150 ET patients showed that JAKV617F-mutated subgroup was associated with advanced age, higher Hgb level and leukocyte counts [12]. In the same study, gender, platelet count, palpable splenomegaly, thrombosis and hemorhage at presentation and at follow-up showed no difference according to JAK2V61F mutation [12].In a meta-analysis however, it was reported that JAK2V617F increased the risk of arterial and venous thrombosis in ET [5].Another meta-analysis including 325 published articles also supported that JAK2V617F-positive ET was associated with increasing odds of thrombosis [26].In a comprehensive study including 395 ET patients,patients with JAK2V617F mutation had significantly higher Hgb level and leukocyte counts but lower platelet counts compared to patients without mutation [27].In a study including 275 ET patients, patients with the JAK2V617F mutation were older and displayed higher Hgb and Hct levels and higher incidence of splenomegaly, but lower platelet count and lower incidence of hemorrhagic events compared with patients without mutation whereas gender, leukocyte count, incidence of thrombosis was comparable between the groups [30].In a study, JAK2V617F-positive ET patients displayed higher Hgb and Hct levels whereas leukocyte and platelet counts, gender, age, disease duration did not differ between JAK2V617F-positive and -negative ET patients [31].In another study including 92 ET patients, significantly higher values were also found for Hgb level and leukocyte count in the JAK2V617F mutation-positive group yet platelet count, LDH level, age, gender and thrombosis did not differ between JAK2V617Fpositive and -negative patients [32]. In another study, it was demonstrated that JAK2V617F-mutated ET patients had advanced age, higher leukocyte count and Hgb level whereas platelet count was similar between the groups [33].In a study including 111 ET patients, the presence of JAK2V617F mutation correlated with older age, higher levels of Hgb and Htc levels, greater probability of having splenomegaly at diagnosis while mutation positive and negative groups showed no difference with respect to gender, probability of hemorrhagic events, leukocyte count and LDH levels [13].…”
Section: Comparison Of Polycythemia Vera Patients According To Jak2v617f Mutationmentioning
confidence: 94%
“…Several studies have reported the comparison of ET patients according to JAK2V617F mutation [4,5,9,12,13,[24][25][26][27][28][29][30][31][32][33][34][35][36].In a study including 218 consecutive ET patients, the presence of JAK2V617F mutation retained a negative prognostic impact for predicting thrombosis [4].In another study including 53 ET patients, JAK2V617F mutation showed significant correlation with higher leukocyte counts, higher Hgb levels and thrombotic events while age, gender, platelet count, frequency of splenomegaly and bleeding events did not differ between the JAK2617F-positive and JAK2V617F-negative ET patients [24]. In a study including 102 ET patients, females were reported to more frequently harbor the JAK2V617F mutation and JAK2V617F-mutated patients were found to be older and had higher leucocyte counts [25].Another study including 150 ET patients showed that JAKV617F-mutated subgroup was associated with advanced age, higher Hgb level and leukocyte counts [12].…”
Section: Comparison Of Polycythemia Vera Patients According To Jak2v617f Mutationmentioning
confidence: 99%
See 1 more Smart Citation